2016
DOI: 10.4236/jep.2016.79107
|View full text |Cite
|
Sign up to set email alerts
|

The Air Quality, Characterization of Polycyclic Aromatic Hydrocarbon, Organic Carbon, and Diurnal Variation of Particulate Matter over Riyadh City

Abstract: Concentrations of airborneparticulate matter (PM10 & PM2.5) were measured over a period extended from January 2012 to October 2013 at two sites: a suburban area, Riyadh airport (AP) and an urban area, King Fahd road district (KF) (densely trafficked site) in Riyadh city, Saudi Arabia. The quality of ambient air using the U.S. Environmental Protection Agency (USEPA) Air Quality Index (AQI) was evaluated during this period. The average AQI values exceeded 100 on 6 months out of 11 in AP district. At KF district … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It can be conclude that the transportation is one of the main causes of pollution in Riyadh. Another study to measure the concentration of PM10 and PM2.5 in Riyad airport (a suburban area) and in King Fahad road district (urban area) located in Riyadh during a period of 22 months, from January 2012 to October 2013 has been conducted by [19]. Results revealed that the AQI values overtook 100 during 6 months in Riyad airport, whereas it surpassed 100 during all month at King Fahad road district.…”
Section: Environmental Deteriorationmentioning
confidence: 99%
“…It can be conclude that the transportation is one of the main causes of pollution in Riyadh. Another study to measure the concentration of PM10 and PM2.5 in Riyad airport (a suburban area) and in King Fahad road district (urban area) located in Riyadh during a period of 22 months, from January 2012 to October 2013 has been conducted by [19]. Results revealed that the AQI values overtook 100 during 6 months in Riyad airport, whereas it surpassed 100 during all month at King Fahad road district.…”
Section: Environmental Deteriorationmentioning
confidence: 99%
“…In world practice, the main way to protect the envi ronment and humans from the harmful effects of industrial waste containing radionuclides is storing them in isolated conditions (underground mined spaces and special storage facilities on the surface) [5,6]. The most promising way to create tailings dams is a combined one, in which the processing waste is placed in a specially equipped natural depression with a dyke [7,8]. In this case, one part is con structed from inert soils, and the other from recycled ore material mixed with a binder component [9,10].…”
Section: Research Of Exiting Solutions Of the Problemmentioning
confidence: 99%
“…In the Arabian Peninsula, information on the spatial and temporal variations of dust properties were recently investigated in Kuwait city and in Al-Ahsa Osasis, Saudi Arabia [9][10][11]. The impact of dust events on local air quality and public health are now becoming of great concern in the Kingdom of Saudi Arabia after the frequent and severe dust storms in recent years [12]. Despite the major efforts focused on measurements of falling dust, the spatial and temporal distribution of mineral dust remains uncertain.…”
mentioning
confidence: 99%